Implementasi Opencart dalam Perancangan Sistem Promosi Karya Siswa Pada Mata Pelajaran Prakarya - Termulo Mitrasyah, Aprian; Annas, Firdaus; Derta, Sarwo; Elin Yuspita, Yulifda (Yayasan Lembaga Studi Makwa, 2024)
Student work in the form of innovations and crafts should be disseminated so as not to become an element of plagiarism for others. While at SMPN7 Bukittinggi student work is still stored manually in a cupboard, so student work is often home and not well maintained. The research aims to design a promotion system for the work of class VIII students in the subject of Crafts at SMPN 7 Bukittinggi so that it can be accessed publicly. The type of research conducted is using the R&D (Research And Development) method using the PPE (Planning, Production, Evaluation) development method. The results of this research are in the form of a website promotion system for student work that has been tested for validity of 0.89 in the “valid” category. The practicality of this system through teacher responses is 0.90 with the category “very practical”. The effectiveness of using the promotion system is 0.5 in the “medium” category. The contribution of this research can increase public access to student work in class VIII at SMPN 7 Bukittinggi so that it can be widely recognized. Abstrak Karya siswa dalam bentuk inovasi dan kerajinan seharusnya dapat disebarluaskan agar tidak menjadi unsur plagiat bagi yang lain. Sementara di SMPN7 Bukittinggi karya siswa masih disimpan secara manual dalam lemari, sehingga karya siswa sering rumah dan tidak terawatt dengan baik. Penelitian bertujuan merancang sistem promosi karya siswa kelas VIII pada mata pelajaran Prakarya di SMPN 7 Bukittinggi agar dapat diakses secara publik. Jenis penelitian yang dilakukan adalah menggunakan metode R&D (Research And Development) menggunakan metode pengembangan PPE (Planning, Production, Evaluation). Hasil peneleitian ini berupa sebuah website sistem promosi karya siswa yang telah teruji kevalidan sebesar 0,89 dengan kategori “valid”. Kepraktisan sistem ini melalui respon guru sebesar 0,90 dengan kategori “sangat praktis”. Keefektifan penggunaaan sistem promosi sebesar 0,5 dengan kategori “sedang”. Kontribusi penelitian ini dapat meningkatkan akses masyarakat luas terhadap karya siswa pada kelas VIII di SMPN 7 Bukittinggi sehingga dapat dikenal secara luas.